Diseño y construcción de una desgranadora de maíz con capacidad de 15 qq/hora - Cholca Cacuango, Luis Christian (2015)
The aims of this Project are to design and built a machine for the process of removing the kernels from corn, by the proper selection of materials and elements, to obtain an efficient and high performance machine with easy handling and clean removal of kernels. The Chapter I describes a study of the general history of corn, including botanical description, characteristics, classification, drying, and methods of kernel removal. Also mentioned the production of corn the national Three alternative designs for kernel removal machines are considered, based on the necessity and demand of the machine. The first alternative considered is a machine with a toothed disk system; as a second option, a kernel removal machine with pin teeth; and finally a machine with axial fins. Finally, the most suitable alternative, which meets all the requirements, was selected. The Chapter II we proceed to the mechanical design of the machine considering strength, speed, power, and adapt to size each component, taking into account external factors for its construction. The general drawings and the design sheets were designed for the corn kernel removal elements. The measurements and tolerances were established. The Chapter III lays out the a cost analysis, aiming to determine the investment amount for the materials, labor, normalized elements, among others, in order to find the total cost of the project. In this chapter also includes the conclusions and recommendations. Finally the annexes contain the technical drawings of the machine as well as extra documents such as photos, charts, etc.